Questioning pattern used by secondary level school teachers in Bangladesh (Dhaka city): an investigation into classroom interaction - Rifat, Afsana (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2017.